2017
DOI: 10.1155/2017/1067598
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol-Induced Alterations of T Cells and Cytokines after Surgery in a Murine Infection Model

Abstract: Background Interactions between alcohol, infection, and surgery and their effect on differentiation and functionality of T helper cells are not yet completely understood. We hypothesized that alcohol and surgery disturb differentiation of T helper cells and contribute to an impaired immune response. Methods Mice were treated with alcohol for two weeks. Saline treatment served as control. Clinical performance and weight were assessed. On day 14, a median laparotomy was performed and animals were challenged with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Consistent with these findings, other groups have found that IL‐17 expression is increased in serum from patients with alcoholic liver disease and that the level of IL‐17 correlates with the degree of liver fibrosis (Ma et al., ). Moreover, chronic alcohol ingestion increased lung‐specific Th17 development and IL‐17 expression in a postsurgical Klebsiella pneumoniae experimental model (Lanzke et al., ). Interestingly, in contrast to a daily chronic alcohol feeding model, there is a down‐regulation of IL‐17 expression 4 to 6 hours following alcohol ingestion in the lungs of mice in an alcohol binge model (Trevejo‐Nunez et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with these findings, other groups have found that IL‐17 expression is increased in serum from patients with alcoholic liver disease and that the level of IL‐17 correlates with the degree of liver fibrosis (Ma et al., ). Moreover, chronic alcohol ingestion increased lung‐specific Th17 development and IL‐17 expression in a postsurgical Klebsiella pneumoniae experimental model (Lanzke et al., ). Interestingly, in contrast to a daily chronic alcohol feeding model, there is a down‐regulation of IL‐17 expression 4 to 6 hours following alcohol ingestion in the lungs of mice in an alcohol binge model (Trevejo‐Nunez et al., ).…”
Section: Discussionmentioning
confidence: 99%